b monk$1 (Bs journey through the bardos of living and dying /sc - Yongey Mingyur (b, 2019)
"In 2011, Mingyur Rinpoche was the respected thirty-six-year-old abbot of three monasteries, a world-renowned meditation teacher, the son of an esteemed meditation master, and a rising star within his generation of Tibetan masters. In Love with the World begins the night that, without telling anyone of his plan, he slips past the monastery gates alone for the first time in his life and sets forth on a wandering retreat, following the ancient practice of holy mendicants. He wanted to throw off his titles and privileges, give up the protections he had always known, and engage in an "ego-killing mission" in order to explore the deepest aspects of his own being and move beyond the grasping self. Yet he immediately discovers that his training has not prepared him to deal with the stench of the third-class train car to Varanasi, or the filthy people around him, or the screeching noise of the train. He has trouble taking off his monk's robes and pays for a cheap hostel rather than sleep on the streets. Soon he becomes deathly ill from food poisoning--and his journey begins in earnest. His lifelong training has prepared him for facing death, and he must now test the strength of his practice. The invaluable lessons he learns from this near-death experience--how we can transform our fear of dying into joyful living--are just what we need to navigate these challenging times. A profoundly moving, unusually candid account by a spiritual master"
Keywords: Yongey Mingyur -- Rinpoche -- 1976.; Buddhist monks -- Biography; Near-death experiences -- Buddhism. -- Religious aspects